Penggunaan antibiotik di dua apotek di Surabaya: identifikasi faktor-faktor yang mempengaruhi kepatuhan pasien - wahyu dewi tamayanti; Windrianita D.M. Sari; Bernadette Dian Novita Dewi (Universitas Ahmad Dahlan, 2016)
Attention to factors that affects proper use of antibiotics need to be conducted to prevent community resistance. This study was aimed to identify factors that affect patients’ compliance of antibiotic use in two pharmacies in Surabaya, Bhumyamca (A) and Tiara 2 (B). Subject of this study was people who purchased antibiotics in the two pharmacies. Data were collected through questionnaires, analyzed using descriptive statistic, and underwent Hosmer and Lemeshow’s multiple regression tests. Factors such as: age, gender, income, duration and pattern of antibiotics use, antibiotics information, complaint and action after antibiotics side effect were observed. There were 94 respondents mainly 26 - 31 of age met the inclusion criteria. Female respondents in A were 74% and 68% in B. Respondents income was 2 to 3 million rupiah, in A (83%) and B (54%). Respondents use antibiotics mainly for 3 to 5 days, in A (47%) and B (50%). Most respondents use antibiotics after meals in A (92%) and B (88%). Antibiotics information was obtained mainly from healthcare providers in A (92%) and B (85%). Respondents had no complaints after antibiotics use in A (87%) and B (73%). Respondents (44%) stop antibiotics when complaints were occurred both in A and B, whereas 56% visited clinician. Respondents in A (86%) and B (89%) were consumed antibiotics in accordance to usage instruction. Conclusively, no factor was associated to patients’ compliance, except pattern of administration in B (0.011).